2016
DOI: 10.1111/asj.12414
|View full text |Cite
|
Sign up to set email alerts
|

Molecular nutrition: Interaction of nutrients, gene regulations and performances

Abstract: Nutrition deals with ingestion of foods, digestion, absorption, transport of nutrients, intermediary metabolism, underlying anabolism and catabolism, and excretion of unabsorbed nutrients and metabolites. In addition, nutrition interacts with gene expressions, which are involved in the regulation of animal performances. Our laboratory is concerned with the improvement of animal productions, such as milks, meats and eggs, with molecular nutritional aspects. The present review shows overviews on the nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The use of antibiotics in animal nutrition has been associated with severe health-related drawbacks (e.g., antibiotic resistance), which has led to bans on their use in several countries. Since then, various novel compounds have been investigated as possible alternatives to antibiotics (Sato, 2016). Immunomodulators are one type of available nutritional molecules that enhance humoral immunity, minimize immunological stress, and protect against disease without decreasing production performance in farm animals (Klasing, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The use of antibiotics in animal nutrition has been associated with severe health-related drawbacks (e.g., antibiotic resistance), which has led to bans on their use in several countries. Since then, various novel compounds have been investigated as possible alternatives to antibiotics (Sato, 2016). Immunomodulators are one type of available nutritional molecules that enhance humoral immunity, minimize immunological stress, and protect against disease without decreasing production performance in farm animals (Klasing, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition is crucial not only for sustaining the prooxidant-antioxidant balance but also for regulating fat metabolic function [ 132 , 133 ]. Reactive oxygen or nitrogen species can modulate primary immune defense, albeit prolonged exposure leads to a disruption of the oxidant/antioxidant network; this imbalance ultimately results in an acceleration of pathological inflammation [ 134 , 135 ].…”
Section: Applications Of L Fermentum In Broiler Ch...mentioning
confidence: 99%
“…The quantities of trehalose found in M. flabellifolius , in many studies, hydrated 26.0 ± 7.7 mgg −1 vs. desiccated 34.7 ± 4.3 mmg −1 dry weight [ 25 ], seem sufficient to illicit some reaction in vivo. In ruminant animals, the authors of [ 26 , 27 ] reported an improvement in oxidative status in blood, milk, and rumen fluid in cows supplemented with trehalose, whilst [ 28 ] reported on reduced medication frequency of pre-weaned calves and growth inhibition of pathogenic bacteria when trehalose was supplemented on milk replacers in pre-weaned calves. Chen et al [ 29 ] highlighted the potential of trehalose as a prebiotic, which encourages growth in the host’s beneficial intrinsic probiotic bacteria.…”
Section: Nutritional Composition Of Myrothamnus Flabellifol...mentioning
confidence: 99%